أزمة التداخل اللغوي بين العامية والفصحى في المدرسة الجزائرية - برماد، أحمد Barmad, Ahmed (جامعة حسيبة بن بوعلي بالشلف, 2018)
تتميز البيئة اللغوية الجزائرية بثراء وتنوع كبيرين، هذا الثراء والتنوع بقدر ما يعبر عن مؤشر صحي للتعايش الاجتماعي والثقافي واللغوي للجماعات اللغوية المشكلة لهذا المجتمع، بقدر ما يشكل تهديدا حقيقيا على هوية الفرد الجزائري خاصة إذا لم يتم استثمار هذا التنوع/ التعدد في المنحى الإيجابي السليم الذي ينتج فردا واعيا بواقعه اللغوي والمحيط الذي يعيش فيه، ويزداد هذا الوضع خطرا في المدرسة إذا لم يتم استثماره استثمارا إيجابيا، والتعامل معه بحذر من أجل تكوين متعلم قادر على تجاوز سلبيات التعدد والازدواجية بكل مظاهرها) الصوتية والصرفية والتركيبية..(، وعليه تضطلع المناهج التعليمية والسياسات اللغوية بمهمة وصف هذا الواقع، وبالتالي تنظيمه على مستوى المحيط التعليمي والاجتماعي والثقافي، وذلك لتجنب تأثيرات التداخل اللغوي خاصة في المراحل العمرية الأولى للفرد الجزائري.
The Algerian linguistic environment is characterized by its richness and diversity. while such diversity reflects the healthy social, cultural, and linguistic coexistence of the linguistic communities of this society, it can threaten the identity of the Algerian individual particularly if it is not exploited in a positive way creating an individual who is conscious of his/ her diverse linguistic landscape as well as the environment where he/she lives. This situation becomes more dangerous in the school if it is not exploited positively and treated with caution and awareness in order to form a learner capable of overcoming the disadvantages of bilingualism and the diversity of the language in all its aspects (phonetics, morphology and syntax). Therefore, it is the educational curricula role to describe this language situation and to organize it at the educational, social, and cultural level to avoid the effects of linguistic interference especially at the early age of the Algerian individual.
Keywords: اللغة العامية; المدرسة الجزائرية; التداخل اللغوي; اللغة الفصحى; الازدواجية اللغوية